Pulmonary artery banding: a 20-year experience at a tertiary care center in a developing country - Ghoussaini, Racha; Zareef, Rana; Makarem, Adham; Younis, Nour; Al Hassan, Sally; El Rassi, Issam; Obeid, Munir; Bitar, Fadi; Arabi, Mariam (Frontiers in Cardiovascular Medicine, 2024)
Aim: Pulmonary artery banding serves as an important palliative procedure used for the management of several congenital heart lesions. This study aims to describe a 20-year experience of pulmonary artery banding at a tertiary care center in a developing country.Methods: This is a retrospective chart review of patients who underwent pulmonary artery banding over a 20-year period between January 2000 and July 2020 in a tertiary care center in a developing country. Data regarding demographics, indications, diagnosis, echocardiographic findings, postoperative complications, hospital stay, and outcomes were recorded.Results: A total of 143 patients underwent pulmonary artery banding between 2000 and 2020, with a decrease from approximately 15 surgeries per year in 2012 to 1-2 surgeries a year in 2020.At the time of banding, the median age of patients was approximately 90 days [interquartile range, IQR, 30-150 days]. Four patients (2.8%) died during the band placement. No significant association was observed between baseline characteristics or type of heart defect at presentation and postoperative morbidity and mortality.Pulmonary artery banding remains useful in a subset of congenital heart lesions and as a surgical palliation, with relatively low mortality, allowing postponement of total correction to a higher weight. This technique continues to be valuable in developing countries or for heart surgical programs with limited resources.